Financial Ratio Analysis: Decision Usefulness for Potential Shareholders' Benefit - Kabir, Musa Usman; Aripin, Norhani; Al-Dhamari, Redhwan Ahmed Ali (UUM Press, 2017)
The certainty of the reliance on the use of financial ratio analysis in making investment decisions by potential investors still remained a mystery. This has to do with the choice of ratios to select when making investment decisions. Many shareholders in Nigeria are uneducated or illiterate, and due to their ignorance, they cannot use ratio analysis in evaluating firms for investment decisions. Thus, this paper explores the concept of financial ratio analysis in terms of the decision usefulness of financial ratios. The paper suggests that the relevant financial information needed for the purposes of making investment decision can be sourced through the use of financial ratio analysis. Therefore, management must ensure that disclosure of comprehensive financial ratios form part of financial statement prepared for the overall appraisal of firms.